2023
DOI: 10.5194/wcd-4-683-2023
|View full text |Cite
|
Sign up to set email alerts
|

Transient anticyclonic eddies and their relationship to atmospheric block persistence

Abstract: Abstract. Atmospheric blocking is a circulation pattern that describes the presence of large-scale, persistent anticyclones, which have the potential to bring severe impacts at the surface. However, the dynamical behaviour of blocks is still not fully understood. For example, the factors that determine the persistence of blocking events are not clear. In this study, the relationship between blocks and smaller-scale transient anticyclonic eddies is examined, with a particular focus on the impact of transients o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, the persistent BE is only reported around the Chukchi Sea for the PV– θ index in summer, up to 8.5 days. Frankly speaking, many previous studies found that BE is the most persistent in winter while the least persistent in summer (Wiedenmann et al ., 2002; Suitters et al ., 2022). We can also understand the shorter‐lived blocking in summer by the large climatological PVy$$ {\mathrm{PV}}_y $$ (Figure S2b in Data S1), which behaves as an unfavourable context for long‐lived and large‐amplitude blocking high.…”
Section: Climatology Of Blocking Episode Characteristicsmentioning
confidence: 99%
“…However, the persistent BE is only reported around the Chukchi Sea for the PV– θ index in summer, up to 8.5 days. Frankly speaking, many previous studies found that BE is the most persistent in winter while the least persistent in summer (Wiedenmann et al ., 2002; Suitters et al ., 2022). We can also understand the shorter‐lived blocking in summer by the large climatological PVy$$ {\mathrm{PV}}_y $$ (Figure S2b in Data S1), which behaves as an unfavourable context for long‐lived and large‐amplitude blocking high.…”
Section: Climatology Of Blocking Episode Characteristicsmentioning
confidence: 99%
“…A further development of the algorithm allows the detection of splitting and merging events along a tracked PVA − . This enables an analysis which examines the role of transient anticyclonic anomalies in feeding a block and is strongly inspired by the work of Shutts (1983), Yamazaki and Itoh (2013) and Suitters et al (2023).…”
Section: Tracking Of Upper-tropospheric Pv Anomalies Linked To Greenl...mentioning
confidence: 99%
“…The breaking of upper-level Rossby waves (further referred to as RWB) has been found as a formation mechanism for blocking over Greenland with predominantly cyclonic RWB towards Greenland (Benedict et al, 2004;Woollings et al, 2008; results on the importance of moist-baroclinic processes by adopting the Eulerian perspective of Teubler et al (2023) into a new quasi-Lagrangian perspective. Previous studies have partly used quasi-Lagrangian approaches to investigate the role of eddy feedback on blocks and, in particular, the role of transient anticyclonic eddies (e.g., Shutts, 1983;Yamazaki and Itoh, 2013;Suitters et al, 2023). By tracing back negative, upper-tropospheric PV anomalies linked to a block over Europe and investigating the relative contributions of dry and moist dynamics using the same piecewise PV tendencies of Teubler et al (2023), the quasi-Lagrangian approach of Hauser et al (2023b) revealed a non-local development of the negative PV anomaly over the western North Atlantic.…”
mentioning
confidence: 99%